Effect of N:P Ratios of the Wastewater Mixture to Growth of Spirulina and N, P Removal Efficiencies after Cultivation - Nguyen, Thuy Nga; Nguyen, Ngoc Chau; Doan, Thi Thai Yen (Old Journal, 2020)
Spirulina is a blue-green alga, which is well-known as a source of protein-rich biomass and well growth in mass scales. The algal biomass can be used as a human diet supplement, animal feeds, and many other applications. Culturing Spirulina in wastewater can utilize nutrients to produce valuable biomass as well as removes pollutants in wastewater. In this study, Spirulina was cultivated in mixtures of diluted rice wine stillage and piggery wastewater for determining the optimal ratio of N:P, collecting protein-rich algae biomass and helping to reduce pollutants in wastewater. The results showed that N:P ratios of wastewater mixture from 16:1 to 20:1 andadding 3 g/L bicarbonate as carbon source was the best conditions for the growth of Spirulina sp.HH. The highest biomass yield was 0.147 g.L⁻¹.day⁻¹, corresponding to the protein content of biomass reaching to 59.8 %. The best removal efficiency of NH₄⁺, NO₃⁻, and PO₄³⁻ were 97.5%, 98.1% and 86.6%, respectively. The study demonstrates the benefit of the reuse of wastewaters to recover the nutrients for producing value-added product.